2018
DOI: 10.1111/ijac.13017
|View full text |Cite
|
Sign up to set email alerts
|

High temperature anti‐oxidation behavior of in situ and ex situ nanostructured C/SiC/ZrB2‐SiC gradient coatings: Thermodynamical evolution, microstructural characterization, and residual stress analysis

Abstract: Nanostructured C/SiC/ZrB2–SiC oxidation protective gradient coating was prepared by a two‐step reactive melt infiltration method. In order to reduce production cost, ZrB2 phase was synthesized by the in situ reactive that included low‐cost ZrO2 and B2O3 powders as raw materials. High‐temperature oxidation behavior of coatings was evaluated by isothermal oxidation test at 1773 K in air for 10 hours. Thermodynamical behavior of the coatings at various temperatures during oxidation test and coating process was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The intensity value of ZrB 2 peak decreased compared with XRD pattern of as‐sprayed coating, which may have been caused by its decomposition and oxidation at high temperature. Since the surface temperature of sample rises, SiC and ZrB 2 phases oxidize and transform to SiO 2 and ZrO 2 according to following reactions:ZrB2normals+5/2normalO2normalg=ZrO2normals+normalB2normalO3normalg 2SiCnormals+3normalO2=2SiO2normall+2COnormalg…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity value of ZrB 2 peak decreased compared with XRD pattern of as‐sprayed coating, which may have been caused by its decomposition and oxidation at high temperature. Since the surface temperature of sample rises, SiC and ZrB 2 phases oxidize and transform to SiO 2 and ZrO 2 according to following reactions:ZrB2normals+5/2normalO2normalg=ZrO2normals+normalB2normalO3normalg 2SiCnormals+3normalO2=2SiO2normall+2COnormalg…”
Section: Resultsmentioning
confidence: 99%
“…The intensity value of ZrB 2 peak decreased compared with XRD pattern of as-sprayed coating, which may have been caused by its decomposition and oxidation at high temperature. Since the surface temperature of sample rises, SiC and ZrB 2 phases oxidize and transform to SiO 2 and ZrO 2 according to following reactions 8 : Surface FE-SEM image of SiC/ZrB 2 coating after 60-second ablation test shows the ablated surface was covered by a relatively dense oxide layer (Figure 20A). Also, pores and cracks are observed in the protective oxide layer.…”
Section: Ablation Mechanism Of Sic/ Zrb 2 Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the solutions is to develop particle‐reinforced Cu matrix composites. ZrC and ZrB 2 possess high hardness, high melting point, excellent thermal stability, and superior electrical conductivity . These properties make them good candidates for acting as the reinforced particles in metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…The flexural strength and fracture toughness of composite were 458 MPa and 6.9 MPa m 1/2 , respectively. Addition of proper amounts of SiC particles can both improve the sinterability and enhance the oxidation resistance of ZrB 2 . Hwang et al reported that the addition of small size SiC particles imparted better oxidation resistance and improved the sinterability of ZrB 2 ceramics.…”
Section: Introductionmentioning
confidence: 99%